2023
DOI: 10.1213/ane.0000000000006737
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Agents as General Anesthetic Adjuncts: Supra-additive and Infra-additive Interactions

Igor Kissin

Abstract: The hypothesis “General anesthesia consists of producing both loss of consciousness and the inhibition of noxious stimuli reaching the brain and causing arousal” was used as a basis for the review of published data on general anesthetic interactions with antinociceptive agents: opioids, α2 adrenergic agonists, and systemic sodium channel blockers. This review is focused on a specific type of anesthetic interaction—the transformation of antinociceptive agents into general anesthetic adjuncts. The primary aim is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 123 publications
0
5
0
Order By: Relevance
“…It has been shown that dexmedetomidine administered through CRI at doses of 0.5, 1, and 3 µg/kg/hour has antinociceptive effects when used concurrently with isoflurane and other general-anesthetic drugs [ 29 , 30 ]. A recent comprehensive review [ 31 ], encompassing both human and animal (rat) studies, highlighted the challenges associated with assessing changes in the requirements of coadministered inhaled anesthetics in the presence of alpha-2 adrenergic agonists such as clonidine and dexmedetomidine. These challenges arise from the intricate interplay between their hypnotic and antinociceptive activities [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that dexmedetomidine administered through CRI at doses of 0.5, 1, and 3 µg/kg/hour has antinociceptive effects when used concurrently with isoflurane and other general-anesthetic drugs [ 29 , 30 ]. A recent comprehensive review [ 31 ], encompassing both human and animal (rat) studies, highlighted the challenges associated with assessing changes in the requirements of coadministered inhaled anesthetics in the presence of alpha-2 adrenergic agonists such as clonidine and dexmedetomidine. These challenges arise from the intricate interplay between their hypnotic and antinociceptive activities [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent comprehensive review [ 31 ], encompassing both human and animal (rat) studies, highlighted the challenges associated with assessing changes in the requirements of coadministered inhaled anesthetics in the presence of alpha-2 adrenergic agonists such as clonidine and dexmedetomidine. These challenges arise from the intricate interplay between their hypnotic and antinociceptive activities [ 31 ]. The complexity is further compounded when these alpha 2 adrenergic agents are administered alone, making it challenging to achieve their target analgesic effects [ 31 ], as observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The IA is a universal method in interaction analysis that can be applied in both clinical and preclinical studies, especially if the tested drugs exerted some measurable effects. At present, the IA is widely used for analysis of interactions between anticancer drugs [18-21], antiseizure medications [22-25], ototoxic drugs [26, 27], antibiotics, and antmicrobial drugs [28,29], and when evaluating the antinociceptive activity of the drugs [30][31][32][33][34][35]. Quite recently, a large-scale and fully automatic IA has been incorporated into in vitro studies for assessing the interactions between anti-cancer drugs and various radiosensitizers to accelerate the discovery of anticancer drugs [36].…”
Section: State Of Knowledgementioning
confidence: 99%